Answer:
[tex](-7)(-1.2)\leftrightarrow 8.4[/tex]
[tex](-2\frac{1}{2})(-2)\leftrightarrow 5[/tex]
[tex](2.5)(-2)\leftrightarrow -5[/tex]
[tex](7)(-1.2)\leftrightarrow -8.4[/tex]
Step-by-step explanation:
Product rule of signs:
(+)(+) = (+)
(+)(-) = (-)
(-)(+) = (-)
(-)(-) = (+)
Using these signs simplify the given expression.
[tex](-7)(-1.2)=8.4[/tex]
It means (-7)(-1.2) is equivalent to 8.4.
[tex](-2\frac{1}{2})(-2)=(-\frac{5}{2})(-2)=5[/tex]
It means [tex](-2\frac{1}{2})(-2)[/tex] is equivalent to 5.
[tex](2.5)(-2)=-5[/tex]
It means (2.5)(-2)- is equivalent to -5.
[tex](7)(-1.2)=-8.4[/tex]
It means (7)(-1.2) is equivalent to -8.4.